Impact of congenital calcitonin deficiency due to dysgenetic hypothyroidism on bone mineral density - Daripa,M. (2004)
The objective of the present study was to determine the effect of chronic calcitonin deficiency on bone mass development. The results of 11 patients with thyroid dysgenesis (TD) were compared to those of 17 normal individuals (C) and of 9 patients with other forms of hypothyroidism (OH): 4 with hypothyroidism due to inborn errors of thyroid hormone synthesis and 5 with Hashimoto's thyroiditis. The subjects received an intravenous calcium stimulus and blood was collected for the determination of ionized calcium (Ca2+), calcitonin, and intact parathyroid hormone. Bone mineral density (BMD) was determined by dual-energy X-ray absorptiometry. After calcium administration the levels of Ca2+ in the two groups of hypothyroidism were significantly higher than in the normal control group (10 min after starting calcium infusion: C = 1.29 ± 0.08 vs TD = 1.34 ± 0.03 vs OH = 1.34 ± 0.02 mmol/l; P < 0.05), and only the TD group showed no calcitonin response (5 min after starting calcium infusion: C = 27.9 ± 5.8 vs TD = 6.6 ± 0.3 vs OH = 43.0 ± 13.4 ng/l). BMD values did not differ significantly between groups (L2-L4: C = 1.116 ± 0.02 vs TD = 1.109 ± 0.03 vs OH = 1.050 ± 0.04 g/cm²). These results indicate that early deficiency of calcitonin secretion has no detrimental effect on bone mass development. Furthermore, the increased calcitonin secretion observed in patients with inborn errors of thyroid hormone biosynthesis does not confer any advantage in terms of BMD.